Building Science, Technology, and Innovation Capacity in Rwanda : Developing Practical Solutions to Practical Problems - Watkins, Alfred; Verma, Anubha (Washington, DC : World Bank, 2012)
The purpose of this report is to show how development issues and policy initiatives shaped the design and structure of the science, technology, and innovation (STI) capacity-building program that eventually emerged from the partnership between the Government of Rwanda and the World Bank. Too often, government STI capacity building programs do not closely link specific STI investments and the country's economic and social development objectives, almost as if investing in science and research and development (R&D) obviated the need to design detailed programmatic linkages and develop mission oriented capacity-building programs. These challenges fall into two broad categories: (a) improving the lives of the rural poor, reducing poverty, and achieving the Millennium Development Goals (MDGs) and (b) generating wealth, diversifying the economy, and supporting private sector initiatives to produce and sell value-added natural resource (mostly agricultural) exports.